Respiratory viruses associated with severe pneumonia in children under 2 years old in a rural community in Pakistan. Issue 11 (3rd May 2016) - Ali, Asad; Akhund, Tauseef; Warraich, Gohar Javed; Aziz, Fatima; Rahman, Najeeb; Umrani, Fayyaz Ahmed; Qureshi, Shahida; Petri, William A.; Bhutta, Zulfiqar; Zaidi, Anita K. M.; Hughes, Molly A.
Abstract : The objective of this study was to determine the incidence of respiratory viruses associated with severe pneumonia among children less than 2 years of age in the rural district of Matiari in Sindh, Pakistan. This study was a community‐based prospective cohort active surveillance of infants enrolled at birth and followed for 2 years. Cases were identified using the World Health Organization's Integrated Management of Childhood Illnesses' definition of severe pneumonia. Nasopharyngeal swabs were obtained for assessment by multiplex RT‐PCR for eight viruses and their subtypes, including RSV, influenza virus, human metapneumovirus, enterovirus/rhinovirus, coronavirus, parainfluenza virus, adenovirus, and human bocavirus. Blood cultures were collected from febrile participants. A total of 817 newborns were enrolled and followed with fortnightly surveillance for 2 years, accounting for a total of 1, 501 child‐years of follow‐up. Of the nasopharyngeal swabs collected, 77.8% (179/230) were positive for one or more of the above mentioned respiratory viruses. The incidence of laboratory confirmed viral‐associated pneumonia was 11.9 per 100 child‐years of follow‐up. Enterovirus/rhinovirus was detected in 51.7% patients, followed by parainfluenza virus type III (8.3%), and RSV (5.7%). Of the uncontaminated blood cultures, 1.4% (5/356) were positive. Respiratory viruses are frequently detected during acute respiratory infection episodes in children under 2 years old in a rural community in Pakistan. However, causal association is yet to be established and the concomitant role of bacteria as a co‐infection or super‐infection needs further investigation. J. Med. Virol. 88:1882–1890, 2016 . © 2016 Wiley Periodicals, Inc.